Peningkatan Pengetahuan Tentang Prinsip Gizi Seimbang pada Siswi Kelas X SMA Sejahtera 1 Depok - Puspita Sari, Dian; Sitoayu, Laras; Meiliana, Yutta Lilin Sabad; Ramadhan, Muhammad Rizzqi (CV. IRA PUBLISHING, 2024)
Indonesia faces three nutritional problems: malnutrition, overnutrition and micronutrient deficiencies. Education is also one of the main factors in dietary issues. This activity aims to increase knowledge about balanced nutrition in young women. This educational activity was carried out face-to-face using a lecture method, PowerPoint media, posters of the contents of my plate, and puzzle game content. This research showed that the average pretest score was 58, and the average post-test score was 76, increasing the score by 18 points. These results prove that students' knowledge regarding nutrition can improve with this activity. Still, it will not change their attitudes and behaviour significantly in a short time, so it is essential to carry out similar educational activities to continue to update and increase nutritional knowledge among teenagers.